Tinjauan Hukum Progresif terhadap Kesepakatan Partial Settlement - Arresti, Fatma Tria; Zuhriah, Erfaniah; Suryanto, Muhammad Handika (Wajah Hukum, 2024)
The The partial settlement provision is a new provision in Supreme Court Regulation (PERMA) No 1 of 2016 which has not been regulated in previous regulations, which is an interesting discussion that must be examined from a progressive legal perspective. The aim of this research is to test progressive legal theory regarding the renewal of partial settlement provisions in Supreme Court Regulation (PERMA) Number 1 of 2016. The research method in this research is normative juridical research with a conceptual approach using library data collection techniques or library research. The results of this research show that the update to Perma Number 1 of 2016 concerning partial settlement provisions has fulfilled the basic ideas of progressive law. Partial Settlement Provisions for a portion of the entire object of a case or lawsuit can create ideal law. The parties can resolve the legal consequences that arise peacefully, after the main lawsuit and will reach a happy ending. Partial settlement provisions will realize the function of mediation, namely as a peaceful settlement and provide ample space for the parties to reach a wise and fair settlement.